Dialysis Distress - Sanjay Kalra; Sourabh Sharma; Manisha Sahay (Journal of the Pakistan Medical Association, 2024)
This communication conceptualizes and characterizes the phenomenon of dialysis distress, commonly encountered in persons living with end stage kidney disease on dialysis. Dialysis distress can be defined as an emotional state, marked by extreme apprehension, anxiety, despair and/or dejection, due to a perceived inability to cope with the challenges and demands of living with dialysis. This concept can be extrapolated to persons who undergo renal replacement therapy such as renal transplant. Dialysis distress should be identified in a timely manner, and managed using appropriate support, counselling and education, delivered in an empathic manner. Keywords: Chronic kidney disease, dialysis, end stage kidney disease, psychosocial aspects, renal replacement therapy